Gene Variants Associated With Venous Thrombosis: A Replication Study in a Brazilian Multicentre Study. (28th October 2020) - Romano, Anna Virgínia Calazans; Barnabé, Aline; Gadelha, Telma Barbosa; Guerra, João Carlos de Campos; Secolin, Rodrigo; Orsi, Fernanda Loureiro de Andrade; Campanate, Gizele de Castro Sousa; Wolosker, Nelson; Annichino-Bizzacchi, Joyce Maria
Single nucleotide polymorphisms (SNP) associated with Venous Thromboembolism (VTE) risk have been identified in European and American populations. Replicate SNPs associated with VTE in a Brazilian multicenter case-control study of the Southeast region. Patients with previous VTE assisted at the Outpatient Clinics of 3 centers of the Southeast Brazilian region were compared to normal controls of the same geographic region. We evaluated 29 SNPs associated with VTE risk in other populations, and 90 SNPs for stratification analysis of the population. Due to high admixture of Brazilian population and lack of previous studies, the calculation of the sample power was performed after genotyping. Sample size, allelic frequency and Hardy-Weinberg equilibrium were estimated. The association and odds ratio analyses were estimated by logistic regression and the results were adjusted for multiple tests using Bonferroni correction. The evaluation of the genetic structure similarity in the cases and controls was performed by AMOVA. 436 cases and 430 controls were included. It was demonstrated that this sample has a statistical power to detect a genetic association of 79.4%. AMOVA showed that the genetic variability between groups was 0.0% and 100% within each group. None of the SNPs showed association with VTE in our population. A Brazilian multicenter case-control study with adequate sample power, high genetic variability though no stratification between groups, showed no replication of SNPs associated with VTE. The high admixture of Brazilian population may be responsible for these results, emphasizing the influence of the population genetic structure in association studies.